2022
DOI: 10.1172/jci158661
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the biogenesis of myeloid-derived suppressor cells enhances immunotherapy efficacy against mammary tumor progression

Abstract: While immune checkpoint inhibitors (ICIs) have transformed the therapeutic landscape in oncology, they are effective in select subsets of patients. Efficacy may be limited by tumor-driven immune suppression, of which 1 key mechanism is the development of myeloid-derived suppressor cells (MDSCs). A fundamental gap in MDSC therapeutics is the lack of approaches that target MDSC biogenesis. We hypothesized that targeting MDSC biogenesis would mitigate MDSC burden and bolster tumor responses to ICIs. We tested a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 89 publications
1
16
0
Order By: Relevance
“…In this study, BRQ-treated MDSCs showed a decrease in the unfolded protein response pathway and downregulation of inducible NOS (iNOS) enzymes, both of which are mechanisms known to increase ROS. These observations provide evidence that reducing oxidative species may also facilitate myeloid differentiation ( 4 ). In another recent report, other mechanisms of BRQ have emerged that elicit direct action on malignant cells, including its ability to increase lipid peroxidation in the inner mitochondrial membrane ( 10 ).…”
Section: Versatility Of Brequinarmentioning
confidence: 67%
See 4 more Smart Citations
“…In this study, BRQ-treated MDSCs showed a decrease in the unfolded protein response pathway and downregulation of inducible NOS (iNOS) enzymes, both of which are mechanisms known to increase ROS. These observations provide evidence that reducing oxidative species may also facilitate myeloid differentiation ( 4 ). In another recent report, other mechanisms of BRQ have emerged that elicit direct action on malignant cells, including its ability to increase lipid peroxidation in the inner mitochondrial membrane ( 10 ).…”
Section: Versatility Of Brequinarmentioning
confidence: 67%
“…In this issue of the JCI , Colligan et al addressed the concept of targeting MDSCs at the bone marrow progenitor phase in a series of preclinical studies ( 4 ). The authors focused on immunotherapy-resistant breast cancer, since MDSCs play a prominent role in this tumor type, lending future translational importance to the study ( 5 ).…”
Section: Versatility Of Brequinarmentioning
confidence: 99%
See 3 more Smart Citations